Effect of coarse aggregate size distribution on fracture toughness of concrete based on boundary effect model. (June 2021) - Zhao, Yanhua; Liu, Yang; Xu, Bohan
Highlights: Fracture toughness of concrete is determined based on boundary effect model. Fracture toughness of concrete is insensitive to coarse aggregate distribution. Tensile strength from boundary effect model is close to flexural tensile strength. Abstract: The paper exams the effect of coarse aggregate size distribution on the fracture toughness of concrete based on the boundary effect model, where four-point bending test was performed on concrete with three coarse aggregate distributions and two water/binder ratios. The choice of the discrete number linking the fictitious crack extension at the peak load and the aggregate size was then discussed. The fracture toughness is found to be insensitive to the coarse aggregate gradation whether for normal or for high strength concrete and can be practically considered to be a constant. A unified value of the discrete number can be adopted for predicting the fictitious crack extension at the peak load, albeit slightly lower for smaller average size of aggregates. Besides, the tensile strength from the boundary effect model is observed to be more close to the flexure tensile strength instead of splitting tensile strength of concrete.